Shared genetic background between SARS-CoV-2 infection and large artery stroke. Issue 8 (October 2022) - Parodi, Livia; Myserlis, Evangelos Pavlos; Chung, Jaeyoon; Georgakis, Marios K; Mayerhofer, Ernst; Henry, Jonathan; Montgomery, Bailey E; Moy, Mandy; Xu, Huichun; Malik, Rainer; Langefeld, Carl D; Dichgans, Martin; et al.
Background and aims: Increased risk of stroke, particularly large artery stroke (LAS), has been observed in patients with COVID-19. The biological processes underlying the observed higher risk are still unknown. We explored the association between stroke subtypes and COVID-19 susceptibility to understand whether biological mechanisms specific to SARS-CoV-2 uptake/infection could be leading to excess stroke risk in this population. Patients and methods: We constructed a polygenic risk score (PRS) of COVID-19 susceptibility and tested its association with stroke subtypes using individual- and summary-level genetic data (SiGN, MEGASTROKE). We generated co-expression networks of genes involved in SARS-CoV-2 uptake/infection ( ACE2, TMPRSS2, BEST3, ISLR2 and ADAM17 ) based on existing tissue expression libraries. Gene-based association testing was performed using S-PrediXcan and VEGAS2. Permutation independence tests were performed to assess SARS-CoV-2-related gene enrichment in stroke and its subtypes. Results: Our PRS demonstrated an association between COVID-19 susceptibility and LAS in SiGN (OR = 1.05 per SD increase, 95% CI: (1.00, 1.10), p = 0.04) and MEGASTROKE (β = 0.510, 95% CI: (0.242, 0.779), FDR-p = 0.0019). The SARS-CoV-2 risk-related ISLR2 co-expression gene network was significantly associated with genetic risk of LAS in aorta, tibial arteries, and multiple brain regions (P < 0.05). Conclusion: Presence of genetic correlation and significant pathway enrichment suggest that increases in LAS risk reported in COVID-19 patients may be intrinsic to the viral infection, rather than a more generalized response to severe illness.